2018
DOI: 10.1111/vde.12696
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver burden in the veterinary dermatology client: comparison to healthy controls and relationship to quality of life

Abstract: Background Skin disease in companion animals often requires long‐term management which may contribute to caregiver burden in the dermatology client. Hypotheses/Objectives We expected greater caregiver burden in dermatology clients relative to healthy control veterinary clients and that no difference would be present between healthy controls and dermatology clients reporting good skin disease control. Within the dermatology sample, we hypothesized that greater caregiver burden would correlate with client percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 15 publications
1
48
0
Order By: Relevance
“…Finally, regarding reference values, because caregiver burden is conceptually due to the burden of providing care during illness, it could be argued that veterinary clients with a healthy companion animal are a suboptimal reference point. However, the present study and prior work demonstrate that when examining self‐reported caregiver burden, a summed total of “0” is actually not typical for owners of a healthy companion animal . In the same way that it is necessary to know the range of values greater than “0” that could be still be considered negative for a given bloodwork titer, it is essential to establish reference values for “normal” burden associated with owning a healthy companion animal.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Finally, regarding reference values, because caregiver burden is conceptually due to the burden of providing care during illness, it could be argued that veterinary clients with a healthy companion animal are a suboptimal reference point. However, the present study and prior work demonstrate that when examining self‐reported caregiver burden, a summed total of “0” is actually not typical for owners of a healthy companion animal . In the same way that it is necessary to know the range of values greater than “0” that could be still be considered negative for a given bloodwork titer, it is essential to establish reference values for “normal” burden associated with owning a healthy companion animal.…”
Section: Discussionmentioning
confidence: 68%
“…geographical regions of the United States with median household income in the range of $62-68 000. 17 Participants were fairly homogeneous in terms of race and sex, with overrepresentation of females and Caucasians relative to the census data for these locations.17 Similar to prior work,4,5,8,16,18 the overrepresentation of Caucasian females could lead to bias in that these individuals might experience burden differently from other groups. Although this is possible, it is also likely that the demographic make-up of our sample is representative of the target population, that is, veterinary clients who choose caregiving over euthanasia when faced with significant illness in a companion animal.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Those owners describe adapting multiple aspects of their own lifestyles to accommodate the reduced exercise capacity, requirements for time-specific medication dosing and frequent veterinary visits required by their dogs. In a series of recent cross-sectional studies, Spitznagel et al [14,[21][22] demonstrated, using scales designed for human patients and carers as well as for pet owners, that owners of pets with a range of chronic illnesses report greater "caregiver burden", psychological distress and a lower quality of life than owners of healthy pets. Where research subjects, in this instance pet owners, are not involved in research design there is a risk that important topics may not be included in tools for their completion leading to poor face validity, a problem common also in human healthcare [23].…”
Section: Introductionmentioning
confidence: 99%